1999
DOI: 10.1002/(sici)1096-9896(199905)188:1<100::aid-path306>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Changes in elemental concentrations are associated with early stages of apoptosis in human monocyte-macrophages exposed to oxidized low-density lipoprotein: an X-ray microanalytical study

Abstract: This study examines ion homeostasis in monocyte–macrophages committed to death by apoptosis. X‐ray microanalysis has been used to demonstrate that intracellular concentrations of potassium decreased whilst those of sodium increased following 3 h of exposure to 100 µg/ml of oxidized low‐density lipoprotein (LDL) in vitro. In contrast, the maximal incidence of cell death, as determined by the inability to exclude trypan blue, was not seen until 24 h of exposure. At 12 h, less than 1 per cent of cells were staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
6
19
0
Order By: Relevance
“…What has separated sodium from potassium during apoptosis is the occurrence of an early increase in sodium during the cell death process. Several initial studies on ions and apoptosis have reported this early increase in intracellular sodium [85][86][87][88]. Additionally, we have shown that apoptotic cells have a significant increase in intracellular sodium that occurs prior to the dramatic loss of cell volume with a variety of apoptotic agents in Jurkat T-cells [89].…”
Section: Sodium As a Signal During Apoptosismentioning
confidence: 57%
“…What has separated sodium from potassium during apoptosis is the occurrence of an early increase in sodium during the cell death process. Several initial studies on ions and apoptosis have reported this early increase in intracellular sodium [85][86][87][88]. Additionally, we have shown that apoptotic cells have a significant increase in intracellular sodium that occurs prior to the dramatic loss of cell volume with a variety of apoptotic agents in Jurkat T-cells [89].…”
Section: Sodium As a Signal During Apoptosismentioning
confidence: 57%
“…Another study with EPXMA reported similar elemental alterations in Na, Cl and K in association with DNA fragmentation detected by terminal transferase-mediated DNA nick-end labelling (TUNEL), a late molecular hallmark of apoptosis. 37 These microanalytical results have recently been confirmed in etoposide-induced apoptosis in prostate cancer cell lines. 38 However, in the LNCaP androgen-sensitive cell line, Cl content increased after androgen withdrawal and etoposide treatment.…”
Section: Discussionmentioning
confidence: 71%
“…*P \ 0.05 compared to the control value measured at 1.5 h. # P \ 0.05 compared to the control value measured at 3 h content of intracellular K ? and Cl -take place during a time period as late as 2-48 h after apoptotic stimulation [39][40][41][42], but also as early as 15-60 min after the stimulation [43,44]. Thus, it appears that apoptosis is coupled to loss or efflux of cellular K ?…”
Section: Discussionmentioning
confidence: 99%